EVALUATION OF TIME AND COST OF DELAY FOR CONSTRUCTION IMPLEMENTATION IN THE BIOMOLECULER LABORATORY BUILDING PROJECT BTKLPP CLASS I MAKASSAR - Hanafi Ashad Ashad; Ratna Musa Musa; Kasmawati Kasmin (Moeslim Indonesian University (UMI), 2020)
In the implementation of a project, it is very rare to find a project that goes exactly as planned. Generally experiencing delays in both time and work progress, but there are also projects that experience acceleration from the initial planned schedule. To avoid losses in the project, we can forecast (forecasting) the cost of completing the project with the Earned Value Concept. The study was conducted to evaluate the time and cost of delays in the construction of the BTKLPP Class I Makassar Biomolecular Laboratory Building Project. The method used for this research is the earned value with a project duration of 22 weeks. From the results of the evaluation using the earned value method, the project completion time from week 1 to week 22 is not in accordance with the initial plan for project implementation, indicating that the PV value is greater than EV, causing a time deviation value or schedule variance or SV from week 1 to 22 almost all of them are negative (-) or SV < 0 this means the project is experiencing delays, and the value of cost variance or cost variance or CV is all positive or CV > 0 means projects with costs under plan , and because the project experienced a delay in completion, the project performance was not good, this was seen in almost all SPI (schedule performance index) values ​​which were less than 1 or SPI values ​​< 1.